Solar energy utilization potential in Jodhpur and New Delhi - GARG , H. P.; KRISHNAN, A. (MAUSAM, 1974)
Average useful solar energies available for utilisation in respect of flat-plate collector kept at optimum tilts in respect of Jodhpur and Delhi were worked out for typical winter and summer months. Based on these average energies generalised design curves for water heating by flat-plate collectors giving the ratio of useful energy collected by the flat- plate collector to the heat removal efficiency factor in terms of inlet temperature rise over ambient temperature have been prepared. Such design curves based on 90 per cent, 50 per cent and 10 per cent exceedance values of useful energies have also been presented in addition to those using average values. With these design curves the flat-plate collector areas required for various heating loads has been estimated for these stations.